Výroba plechu držáku projektoru - Starý, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Diplomová práce předkládá návrh technologie výroby držáku projektoru z ocelového plechu 11 321 o tloušťce 2 mm. Vzhledem k velkému počtu kusů a výrobním tolerancím byla variantním řešením zvolena jako nejoptimálnější možnost výroba postupovým sdruženým nástrojem s pomocí technologií stříhání a ohýbání. Byla posouzena technologičnost, určen postup výroby a provedeny technologické a kontrolní výpočty. Dle celkové tvářecí síly 2 000 kN byl zvolen mechanický lis LDC 250 od firmy Šmeral Brno a.s. s nominální silou 2 500 kN a jako polotovar pás plechu ze svitku, který bude do stroje dodáván pomocí podávacího zařízení. Součást bude vyráběna v šesti krocích. Technicko-ekonomickým zhodnocením byla jeho finální cena při velikost série 250 000 kusů za rok stanovena na 30,80 Kč.

The diploma thesis presents technology production design of a data projector bracket made of 2 mm thickness 11 321 steel plate. Considering the large production quantity and maximum tolerable deviations, a progressive die tool along with cutting and bending was chosen as the optimal solution for this type of production, based on a variant solution. Technological aspects were assessed, the production process was established, and technological and control calculations were performed. According to the total forming force of 2 000 kN, the LDC 250 mechanical press with a nominal force of 2 500 kN, manufactured in Šmeral Brno a.s., was chosen to meet the production requirements. The chosen material in a form of metal sheet coils will be supplied to the machine by a feeding device. The article will be manufactured in six steps. Based on technical-economic evaluation, the final price of a single piece in a series of 250 000 pieces per year was set at 30,80 Kč.
Production of a part of the data projector bracket
Keywords: postupový sdružený nástroj; stříhání; ohýbání; ocel 11 321; plech; progressive die tool; cutting; bending; 11 321 steel; sheet metal